Transnational corporations in Argentina, 1976-1983 - Daniel Azpiazu; Eduardo Basualdo; Bernardo Kosacoff (CEPAL Review, 1986)
The purpose of this article is to analyse the more salient features of the performance and evolution of foreign capital in the Argentine economy during the military government which was in power from 1976 to 1983. In the introduction, a brief summary of the long-term situation is given, with emphasis being placed on the fundamental role which foreign capital has played in the economic development of Argentina throughout its history. Section One contains a discussion of the evolution of foreign investments authorized to establish themselves in the country, special aspects of their capital contributions and their distribution by sector and country of origin and, finally, an analysis of those investments which were channelled to the financial sector and those which originated in the United States.